The Therapeutic Use of Ayahuasca - Labate, Beatriz Caiuby; Cavnar, Clancy; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book presents a series of perspectives on the therapeutic potential of the ritual and clinical use of the Amazonian hallucinogenic brew ayahuasca in the treatment and management of various diseases and ailments, especially its role in psychological well-being and substance dependence. Biomedical and anthropological data on the use of ayahuasca for treating depression, PTSD, and substance dependence in different settings, such as indigenous contexts, neo-shamanic rituals, contemporary therapeutic circles, and in ayahuasca religions, in both South and North America, are presented and critiqued. Though multiple anecdotal reports on the therapeutic use of ayahuasca exist, there has been no systematic and dense reflection on the topic thus far. The book brings the therapeutic use of ayahuasca to a new level of public examination and academic debate. The texts in this volume stimulate discussion on methodological, ethical, and political aspects of research and will enhance the development of this emergent field of studies.
Therapeutic Applications of Ayahuasca and Other Sacred Medicines -- The Therapeutic Potentials of Ayahuasca in the Treatment of Depression -- Ayahuasca as a Candidate Therapy for PTSD -- Moments of Insight, Healing and Transformation: A Cognitive Phenomenological Analysis -- Healing with Ayahuasca: Notes on Therapeutic Rituals and Effects in European Patients Treating Their Diseases -- Ayahuasca and the Treatment of Drug Addiction -- Hypotheses Regarding Ayahuasca s Potential Mechanisms of Action in the Treatment of Addiction -- Therapist and Patient Perspectives on Ayahuasca-Assisted Treatment for Substance Dependence -- Effect of Santo Daime Membership on Substance Dependence -- Experience of Treatment with Ayahuasca for Drug Addiction in the Brazilian Amazon -- Assessment of the Psychotherapeutic Effects of Ritual Ayahuasca Use on Drug Dependency: A Pilot Study -- Healing with Yagé: An Interview with Taita Juan Bautista Agreda Chindoy.
Keywords: Medicine; Toxicology; Alternative medicine; Psychopharmacology; Psychotherapy; Biomedicine; Pharmacology/Toxicology.; Complementary & Alternative Medicine; Psychopharmacology; Psychotherapy